NOTCH1, NOTCH3, NOTCH4, and JAG2 protein levels in human endometrial cancer - Aušra Sasnauskienė; Violeta Jonušienė; Aurelija Krikštaponienė; Stasė Butkytė; Daiva Dabkevičienė; Daiva Kanopienė; Birutė Kazbarienė; Janina Didžiapetrienė (Medicina, 2014)
Background and objective: Notch signaling is a conserved developmental pathway, which plays an important role in the regulation of cell proliferation, differentiation and death. Deregulation of Notch pathway has been connected with the carcinogenesis in a variety of cancers. The aim of this study was to investigate the level of the Notch signaling pathway proteins (NOTCH1, 3, 4 and JAG2) in the samples from human endometrial cancer. Materials and methods: The amount of the Notch receptors NOTCH1, 3, 4 and ligand JAG2 protein was determined by Western blot analysis in the samples from stage I endometrial cancer and adjacent nontumor endometrial tissue of 22 patients. Results: The level of NOTCH4 receptor was 1.7 times lower in stage I endometrial cancer as compared with the healthy tissue of the same patients (P = 0.04). The protein level of ligand JAG2 was significantly reduced by 2.5 times in stage IB endometrial adenocarcinoma samples (P = 0.01). It was reduced in the majority of stage IB adenocarcinomas. There were no significant changes in the protein amount of NOTCH1 and NOTCH3 receptors comparing stage I endometrial adenocarcinoma and healthy tissues. Conclusions: The reduced amount of NOTCH4 and JAG2 proteins and the decreased level of mRNA coding Notch proteins, as reported in our previous studies, supports the notion that Notch pathway has rather tumor-suppressive than oncogenic role in human endometrial cancer cells. It suggests that Notch pathway activation is a potential therapeutic target.